Pendekatan dalam Studi Mahasiswa Bahasa dan Sastra Arab UIN Sunan Gunung Djati Bandung (Gunung Djati Conference Series, 2025)
This study discusses the diversity and depth of research conducted by students of the Arabic Language and Literature Department at UIN Sunan Gunung Djati Bandung, particularly in the fields of linguistics and literature. The aim of the research is to evaluate the academic contributions of the students as well as the relevance of their findings to academic needs and current global issues. The method used is qualitative descriptive, by analyzing student publications from SINTA-accredited journals ranging from SINTA 2 to SINTA 6. The results show that students possess a strong command of theoretical knowledge and are capable of connecting language, literature, and culture in a modern context. However, there are still opportunities to develop more applied and interdisciplinary research, as well as to increase the number of publications in international journals with broader coverage. The conclusion of the study highlights the importance of innovation and cross-disciplinary collaboration to strengthen academic impact while providing tangible benefits to society. The contribution of this research is to provide a comprehensive overview of the development and potential of student research in Arabic Language and Literature at the higher education level.